2021
DOI: 10.1021/acs.jpcb.0c11024
|View full text |Cite
|
Sign up to set email alerts
|

Kosmotropic Electrolyte (Na2CO3, NaF) Perturbs the Air/Water Interface through Anion Hydration Shell without Forming a Well-Defined Electric Double Layer

Abstract: The ion-driven electric double layer (EDL) and the structural transformation of interfacial water are implicated in unusual reaction kinetics at the air/water interface. By combining heterodyne-detected vibrational sum frequency generation (HD-VSFG) with differential spectroscopy involving simultaneous curve fitting (DS-SCF) analysis, we retrieve electrolyte (Na2CO3 and NaF)-correlated OH-stretch spectra of water at the air/water interface. Vibrational mapping of the perturbed interfacial water with the hydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 80 publications
2
6
0
Order By: Relevance
“…The theoretical calculation by the Skinner group (Figure , lower right) predicted a blue shift and narrowing upon the isotopic dilution for the hydrogen-bonded OH band, which is not compatible with our experimental data even if we take Fresnel factors into account. Recent independent experimental studies by four groups are compatible with our experimental spectra, again confirming that the calculated spectra do not reproduce the experimental data. It is also noted that Nagata and co-workers reported the vanishing of the 3200 cm –1 band upon the dilution in their theoretical calculation, which is inconsistent with the experimental data as well.…”
supporting
confidence: 69%
“…The theoretical calculation by the Skinner group (Figure , lower right) predicted a blue shift and narrowing upon the isotopic dilution for the hydrogen-bonded OH band, which is not compatible with our experimental data even if we take Fresnel factors into account. Recent independent experimental studies by four groups are compatible with our experimental spectra, again confirming that the calculated spectra do not reproduce the experimental data. It is also noted that Nagata and co-workers reported the vanishing of the 3200 cm –1 band upon the dilution in their theoretical calculation, which is inconsistent with the experimental data as well.…”
supporting
confidence: 69%
“…17,18 During the last few decades, the pronounced surface activity of long-chain carboxylic acids and long-chain carboxylates inspired many studies of the acid/base equilibrium, the surface propensity, and the orientation properties of these systems in dependent of the chain length, the concentration and the pH. [19][20][21][22][23] Surfacespecific X-ray photoelectron spectroscopy (XPS) studies showed that the surface propensity increases with increasing chain length. 24 Furthermore, it has been shown that carboxylic acid has a higher surface affinity than its conjugate carboxylate anion.…”
mentioning
confidence: 99%
“…Imχ (2) spectra of the aqueous interfaces were recorded with a home-built broadband HD-VSFG spectrometer. Details of the HD-VSFG spectrometer have been described elsewhere. Briefly, a Ti:sapphire regenerative amplifier laser system (Trident M (V2), Amplitude Technology; 3.0 W, 800 nm, 1 kHz, ∼ 50 fs) with frequency conversion units (TOPAS-C, NDFG, Light Conversion) was used as the light source. A spectrally narrow visible pulse (ω VIS ; center wavelength 800 nm; fwhm ∼16 cm –1 , energy ∼10 μJ/pulse) and a broadband IR (ω IR ; 5 μJ/pulse, fwhm ∼300 cm –1 for the center wavelength of 3100 nm) pulse were spatially and temporally overlapped onto the aqueous sample surface to generate the sample sum frequency (SF sample ; ω SF = ω VIS + ω IR ).…”
Section: Materials and Methodsmentioning
confidence: 99%